A quantitative analysis of factors which influence supplement use and doping among adolescent athletes in New Zealand - Clancy, S.; Borotkanics, R.; Millar, S. K.; Oldham, A. R. (Frontiers in Sports and Active Living, 2023)
Objectives: Doping is a maladaptive behaviour which poses numerous risks and potentially enhances athletic performance while supplement use poses threats of positive, yet inadvertent, doping control results. Investigation is required to understand factors that influence adolescent supplement use and doping in New Zealand (NZ).